Large amplitude inversion tunneling motion in ammonia, methylamine, hydrazine, and secondary amines: From structure determination to coordination chemistry - Nguyen, Ha Vinh Lam; Gulaczyk, Iwona; Kręglewski, Marek; Kleiner, Isabelle (Coordination chemistry reviews, 2021)
[Display omitted] •Molecular structures of ammonia derivatives captured by spectroscopy.•Tunneling motion as essential information to understand coordination complexes.•Structures and internal dynamics from experimental and theoretical points of view.•Using the structures of isolated ligand to determine the structure of complexes. Inversion tunneling in a symmetric double minimum potential is a challenging large amplitude motion problem which causes all rotational energy levels to split into a symmetric and an antisymmetric level. Not like other types of large amplitude motion such as internal rotation, inversion tunneling appears much rarer, but the fundamental knowledge gained from this motion is essential to understand the complex structures in coordination chemistry. A double minimum potential needed for inversion tunneling requires the symmetry of the frame to which the inversion object is attached to be Cs or higher, while there is no restriction on the symmetry of the frame for internal rotation. This review summarizes four most classic examples of molecules featuring inversion tunneling motion and their coordination complexes. The textbook example, ammonia, with its umbrella motion during which the nitrogen atom passes from one side of the plane formed by the three hydrogens to the other, will be presented with information on its group theoretical considerations, theoretical studies, electronic ground state spectra in the infrared range, and its coordination complexes, especially those formed with calcium and copper. In the second classic example, methylamine, CH3NH2, the inversion motion of the amino group –NH2 is coupled with a methyl internal rotation –CH3. The spectrum of methylamine can be treated using a tunneling formalism applying the G12 permutation-inversion symmetry group. Extensive studies on the ground state, the first and second excited torsional states ν15, the inversion wagging state ν9, and the C-N stretching band ν8 exist along with their combinations. Pertubations and blends have made the analysis of methylamine very challenging. The third subject is on hydrazine with complex internal dynamics governed by three large amplitude motions: two –NH2 tunneling motions and an internal rotation (torsion) of the two amino groups around the N-N bond. Regarding the spectrum of hydrazine, the vibrational ground state lies in the microwave region. The first, second, and third excited torsional band ν7, symmetric wagging ν6, and asymmetric wagging ν12 are found in the infrared range. Group theoretical treatment and tunneling formalism can only be used to fit sub-bands individually, while global fits still remain a difficult task. Metal complexes with hydrazine and methylamine are introduced, proving the importance of spectroscopic understanding of molecular structures for the knowledge of coordination chemistry. Finally, secondary amines feature inversion tunneling of the hydrogen atom attached to the nitrogen, which is accompanied by two methyl internal rotations but not coupled with them so that they can be treated separately. For this class of molecules, only spectra of the vibrational ground state in the microwave domain will be considered.